Electrochemical investigations of carbon‐based conductive coatings for application as anodes in ICCP systems of reinforced concrete structures. Issue 7 (8th July 2014) - Poltavtseva, M.; Ebell, G.; Mietz, J.
<x xml:space="preserve">Abstract</x> Carbon‐based conductive coatings are complex composites, consisting of an organic or inorganic binder and conductive carbon components, for application as anodes in impressed current cathodic protection systems of reinforced concrete structures. The electrochemical properties of three coatings at different humidity and in saturated calcium hydroxide solution were studied by electrochemical methods, such as electrochemical impedance measurement, measuring of open circuit potential over time and galvanostatic polarization. The dissolved organic and inorganic carbons in electrolyte solution were quantified by using a photometric method. The structures of the coatings were investigated before and after the electrochemical tests by microscopy and scanning electron microscope/EDX analysis. The results of the electrochemical impedance measurements show that the tested coatings all have a relatively low resistance, which is between 100 and 200 Ω. The binder and the surface porosity influence the degradation behavior of those coatings. Especially the organic binder reacts with the strong alkaline medium under dissolving of organic carbon.